2015
DOI: 10.15446/profile.v17n2.47510
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Foreign Language Learners in a Web 2.0-Mediated Collaborative Learning Process

Abstract: <p>The purpose of this action research was to explore the types of interactions that foreign language learners experience while using a wiki as a supporting tool for a face-to-face research course. This design allowed me to play a dual role: first, I studied my own classroom setting and students. Second, I implemented a pedagogical intervention based on a collaborative online learning interaction. The data were gathered from participants’ posts, and the findings revealed that class tasks promoted an asyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Fadzil (2018) studied Malaysian students' use of infographics to improve interest in the learning process and perceived that infographics adequately represented the facts. Cote Parra (2015) found that infographics improve students' learning skills and interaction, and a study in Saudi Arabia found students evaluated and approved of infographics compared with traditional text-based materials (Dahmash, Al-Hamid, & Alrajhi, 2017).…”
Section: Incorporating Dmmc Into Esp Teaching and Assessmentmentioning
confidence: 99%
“…Fadzil (2018) studied Malaysian students' use of infographics to improve interest in the learning process and perceived that infographics adequately represented the facts. Cote Parra (2015) found that infographics improve students' learning skills and interaction, and a study in Saudi Arabia found students evaluated and approved of infographics compared with traditional text-based materials (Dahmash, Al-Hamid, & Alrajhi, 2017).…”
Section: Incorporating Dmmc Into Esp Teaching and Assessmentmentioning
confidence: 99%
“…Asimismo, la relación entre aprendizaje colaborativo y tecnología digital es estrecha, a tal punto que una de las áreas de investigación derivada de la colaboración asistida por computadora -computer supported collaboration (CSC)-es precisamente el aprendizaje colaborativo asistido por computadora -computer supported collaborative learning (CSCL)-, que tiene como objetivo mejorar el proceso de aprendizaje y los resultados académicos de los estudiantes con la ayuda de la tecnología (Cote-Parra, 2015).…”
Section: La Evolución De Los Medios Hacia El Aprendizaje Móvilunclassified
“…El desarrollo de la habilidad escrita del idioma inglés se encuentra estrechamente relacionado con el uso de tecnologías. Cote (2015) reveló que las actividades de clase permitieron una interacción asincrónica voluntaria entre los participantes, en la cual ellos compartieron saberes y experiencias, a la vez que expresaron opiniones y puntos de vista que les permitieron participar activamente en la clase presencial. Desde este punto de vista, se debe hacer un análisis de otros beneficios que pudiera aportar la mediación con tecnologías, además de proporcionar apoyo en el aprendizaje de un tema en específico.…”
Section: Conclusionesunclassified